2020
DOI: 10.1021/acs.joc.9b03210
|View full text |Cite
|
Sign up to set email alerts
|

Axial Chirality around N–P Bonds Induced by Complexation between E(C6F5)3 (E = B, Al) and an N-Phosphine Oxide-Substituted Imidazolinylidene: A Key Intermediate in the Catalytic Phosphinoylation of CO2

Abstract: Complexation-induced axial chirality around an N–P bond occurs upon the predominant coordination of the N-phosphinoyl group in the N-phosphine oxide-substituted imidazolinylidene (SPoxIm) to B­(C6F5)3. (R a) and (S a) atropisomers of (κ-O-SPoxIm)­B­(C6F5)3 were observed independently in the single-crystal lattice and the optimized gas-phase structure. Experimental and theoretical studies confirmed that this axial chirality arises from the restricted rotation around the N–P bond, caused by the steric repulsion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…For example, the complexation of (S)PoxIms with E(C 6 F 5 ) 3 (E=B, Al) furnishes ( κ ‐ O ‐(S)PoxIm)E(C 6 F 5 ) 3 complexes that contain the carbene carbon atoms (Figure 1a). In the case of SPoxIm, axial chirality was induced around the N−P bond in the solid state [4e] . These examples demonstrate that complexation between Lewis acids and the phosphinoyl oxygen atom of (S)PoxIms can afford novel functionalized carbene species.…”
Section: Figurementioning
confidence: 81%
See 1 more Smart Citation
“…For example, the complexation of (S)PoxIms with E(C 6 F 5 ) 3 (E=B, Al) furnishes ( κ ‐ O ‐(S)PoxIm)E(C 6 F 5 ) 3 complexes that contain the carbene carbon atoms (Figure 1a). In the case of SPoxIm, axial chirality was induced around the N−P bond in the solid state [4e] . These examples demonstrate that complexation between Lewis acids and the phosphinoyl oxygen atom of (S)PoxIms can afford novel functionalized carbene species.…”
Section: Figurementioning
confidence: 81%
“…Although significant differences are not observed in the bond lengths and angles, ( S a )‐ 3 b and ( R a )‐ 3 b exhibit different C1−N1−P−N3 torsion angles (( S a )‐ 3 b : +161.0(3)°; ( R a )‐ 3 b : −164.9(3)°), demonstrating the presence of axial chirality around their N1−P bonds in the crystalline lattice. The absolute values of these torsion angles are inequivalent, whereas the ( S a ) and ( R a ) atropisomers found in the single‐crystal of ( κ ‐ O ‐SPoxIm)E(C 6 F 5 ) 3 (E=B, Al) exhibited identical structural parameters, including the absolute values of the C−N−P−O torsion angles [4e] . To gain further insight into the axial chirality observed in 3 b , DFT calculations were carried out for both ( S a )‐ 3 b and ( R a )‐ 3 b at the ω B97X‐D/6‐311G(d,p)// ω B97X‐D/6‐31G(d) level of theory (gas phase).…”
Section: Figurementioning
confidence: 95%
“…The molecular structure of (R a )-2aB 2 is shown in Fig. 2b and demonstrates a rare example of complexation-induced N-P axial chirality 29 . As the reaction progressed, 2aB 2 was converted to 3aB 2 and 4a; 2aB 2 was fully consumed within 6 h to afford these compounds in 75% and 25% yield, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…1) that are comprised of N-phosphine-oxide-substituted imidazolylidenes (PoxIms; 1) and B(C 6 F 5 ) 3 (B 1 ). Here, the revival of the FLP from the CLA is closely controlled by a thermally induced conformational isomerization of the N-phosphinoyl moiety 17,[27][28][29][30] . In 2018, Stephan et al reported a system to control the generation of FLPs from CLAs via a light-induced E/Z isomerization of (C 6 F 5 ) 2 B((p-Tol)S)C = CCH( t Bu) 31 .…”
mentioning
confidence: 99%
“…2A) (25,26). To date, (S)PoxIms have demonstrated various coordination modes toward metals, including coordination by only the carbene atom (-C) (27,28), by only the N-phosphinoyl oxygen atom (-O) (29,30), and by both the carbene and oxygen atoms (-C,O) (31,32); however, dynamic coordination exchange between the -C and -C,O modes remains unknown.…”
Section: Main Textmentioning
confidence: 99%